Visual reversals and biases while observing ambiguous spinning biological motion and rigid structure-from-motion - Leo Poom; Wilma Loogna; Edvin Carstensen (PLoS ONE, 2026)
We examined perceived reversal rates and biases as observers viewed four ambiguous, motion-defined depth asymmetric point-light stimuli: a biological motion stimulus in the form of a spinning point-light walker (PLW), a rigidly spinning human figure, a spinning half-cylinder, and a wobbling slanted cylinder. The last three are rigid structure-from-motion (SFM) stimuli. We analysed angular reversal distributions to assess perceptual biases: facing-the-viewer (FTV), convexity, and depth-symmetry biases. The PLW showed the highest reversal rate and a strong FTV bias, though responses were bimodal, some observers experienced reversals every half-turn, others rarely. The rigid human figure showed a weak FTV bias. The spinning half-cylinder resulted in an initial convexity bias, but the occurrence of reversals following the initial percept instead revealed a novel “edge-in-front” bias. The wobbling cylinder showed no angular bias, and had the fewest reversals, likely due to persistent depth asymmetry throughout its motion, and/or that the wobbling prevent adaptation-recovery cycles of neural populations tuned to opposite spinning directions. Correlation analyses revealed shared mechanisms among spinning stimuli, but not with the wobbling cylinder. These findings highlight how shape and motion jointly influence perceptual reversals, refining models of bistable perception and individual variability.